Structural displacement of prestressed concrete sleepers subjected to six coaches commuter load at Pinang Tunggal and Kobah - Mashita Harun; Mohd Ikmal Fazlan Rozli; Kay Dora Abd Ghani; Norliyati Md.Amin (Penerbit Universiti Kebangsaan Malaysia, 2022)
Nowadays, train is one of an effective transportation in Malaysia. Commuter started the operation at Central Region had extended the operation at Northern Region in 2015.Since the volume of passengers were increasing every year, it caused railway track need to be maintenance frequently due to the displacement of concrete sleeper on railway track. According KTMB representative, the displacement happened depend on the soil condition. However, this study figured out the structural displacement concrete sleeper under different of soil condition. A site investigation had been carried out along railway track from Butterworth to Alor Setar. In this study had selected Pinang Tunggal the subsoil condition silty sand in category which displacement 7.40mm and Kobah the subsoil condition under soft clay, the displacement 0.15mm accordingly. The tools that had been used in this site investigation such as vibrator machine and piezometer. The captured records transferred to software called as Dewesoft to measure the displacement of concrete sleeper. From the result had been plotted on the graph showed sandy silt had shown the highest displacement compared with the soil condition soft clay. Therefore, the roof cause of displacement of concrete sleeper at railway track may cause the water table in the subsoil. This study would assist the authority to plan the maintenance on railway track.